Evidence for Conformational Mechanism on the Binding of TgMIC4 with beta-Galactose-Containing Carbohydrate Ligand - Santos, Adriano [UNESP]; Carvalho, Fernanda C. [UNESP]; Roque-Barreira, Maria-Cristina; Zorzetto-Fernandes, Andre Luiz; Gimenez-Romero, David; Monzo, Isidro; Bueno, Paulo R. [UNESP] (Amer Chemical Soc, 2015)
A deeper understanding of the role of sialic/desialylated groups during TgMIC4-glycoproteins interactions has importance to better clarify the odd process of host cell invasion by members of the apicomplexan phylum. Within this context, we evaluated the interaction established by recombinant TgMIC4 (the whole molecule) with sialylated (bovine fetuin) and desialylated (asialofetuin) glycoproteins by using functionalized quartz crystal microbalance with dissipation monitoring (QCM-D). A suitable receptive surface containing recombinant TgMIC4 for monitoring beta-galactose-containing carbohydrate ligand (limit of quantification similar to 40 mu M) was designed and used as biomolecular recognition platform to study the binding and conformational mechanisms of TgMIC4 during the interaction with glycoprotein containing (fetuin), or not, terminal sialic group (asialofetuin). It was inferred that the binding/interaction monitoring depends on the presence/absence of sialic groups in target protein and is possible to be differentiated through a slower binding kinetic step using QCM-D approach (which we are inferring to be thus associated with beta-galactose ligand). This slower binding/interaction step is likely supposed (from mechanical energetic analysis obtained in QCM-D measurements) to be involved with Toxoplasma gondii (the causative agent of toxoplasmosis) parasitic invasion accompanied by ligand (galactose) induced binding conformational change (i.e., cell internalization process can be additionally dependent on structural conformational changes, controlled by the absence of sialic groups and to the specific binding with galactose), in addition to TgMIC4-glycoprotein solely recognition binding process.